Multiple solutions for flow mode−transition in an inclined cavity generated by natural convection - Zellouf, Miloud; Moummi, Noureddine; Labed, Adnane; Aoues, Kamel (Journal of Applied Engineering Science & Technology; Vol 2 No 2 (2016), 2016)
An investigation of natural convection in a rectangular cavity (AR = 4) filled with air (Pr = 0.71) heated from the side with adiabatic horizontal walls is carried out numerically. To describe the flow regime, we propose a description of the influence of the angle of inclination and Rayleigh number on the flow patterns likely to develop in this configuration. The numerical analysis of the governing equations of the problem is based on finite volume method with non-staggered grids arrangement and is solved through the iterative SIMPLEC algorithm. Results indicate that the angle of inclination has a significant effect on flow mode transition. The existence of multi-steady solutions closely depends on the value of the Rayleigh number. For that the Hysteresis phenomenon (multi−steady solutions) for Ra ≥ 2000 are demonstrated and parameter maps of Ra vs. φ are proposed.
Keywords: Natural convection, Inclined cavity, Hysteresis phenomenon, Flow mode transition, Sizing calculations